Comprehensive physical rehabilitation of patients with heart failure: impact on clinical and functional status and analysis of problems related to the enrollment - Yu. L. Begrambekova; N. A. Karanadze; A. G. Plisyuk; Ya. A. Orlova (Российский кардиологический журнал, 2022)
Aim. To evaluate functional, clinical and psychological status of patients with class II-III heart failure, who underwent comprehensive cardiac rehabilitation program.Material and methods. Patients of both sexes with class II-III heart failure who met the inclusion criteria, did not have the exclusion criteria, and signed informed consent were included. The training process consisted of a 4-week respiratory muscle (RM) training using the THRESHOLD® IMT breathing trainer followed by a 12-week moderate intensity aerobic exercise (AE). AE were conducted under the supervision of an instructor 3 times a week for 40 minutes. RM training was carried out by patients at home on their own 5-7 times a week. Minnesota Living With Heart Failure Questionnaire (MLwHFQ.23) was used to assess quality of life. In addition, we applied Hospital Anxiety and Depression Scale (HADS). The evaluation was performed before the start of the study (visit 1), after 4 weeks of respiratory training (visit 2) and at the end of 16 weeks of AE (visit 3). The baseline characteristics of patients who were screened and not enrolled in the study were compared with those who participated in training.Results. A total of 102 patients were included in the study (passed the first visit). Subsequently, for various reasons, including due to the pandemic, 82 patients refused to participate in the study. Only 20 patients participated in RM training for 4 weeks followed by a 12-week cycle of moderate-intensity AR (median age, 67,0 (58,7-74,3) years; men, 70%; Δ peak oxygen uptake (VO2peak) (1-2) =1,1, p=0,3863; ΔVO2 peak (1-3) =2,3 ml/kg/min, p=0,139. During 16-week training, we revealed an increase in expiratory muscle strength (EMS) (ΔEMS =10 cmH2O (p=0,037), six-minute walk test (6MWT) (Δ6MTX=60 meters, p=0,005), and SHOKS score (p=0,0117), as well as improvement in anxiety and depression symptoms (ΔHADS =-2 points, p=0,0346). Patients who refused to be included in the study were older, had lower blood pressure, and had a worse quality of life. The groups did not differ significantly in other clinical, functional and laboratory parameters.Conclusion. Patients’ motivation to exercise was associated with younger age and better subjective health perception and did not depend on objective status. In patients undergoing a comprehensive rehabilitation program, there was a significant change in RM strength, as well as an increase in 6MWT distance, clinical and psychological status already at the stage of respiratory training. This trend continued at the AE stage as well.